Zinc(II)‐Dipicolylamine Coordination Nanotheranostics: Toward Synergistic Nanomedicine by Combined Photo/Gene Therapy. (5th December 2018) - Chu, Chengchao; Ren, En; Zhang, Yunming; Yu, Jingwen; Lin, Huirong; Pang, Xin; Zhang, Yang; Liu, Heng; Qin, Zainen; Cheng, Yi; Wang, Xiaoyong; Li, Wei; et al.
Abstract: We report the rational design of coordination‐driven self‐assembly metal–organic nanostructures for multifunctional nanotheranostics. Zinc(II) coordination‐based nano‐formulations capable of loading indocyanine green (ICG) and therapeutic genes were prepared to achieve a fluorescence/photoacoustic imaging‐guided combination photo/gene therapy strategy. We showed the enhanced theranostic capability of zinc(II)‐dipicolylamine‐assisted assembly of ICG, as well as simultaneous targeted gene delivery in an experimental mouse model of cancer. Such a co‐assembly strategy provides a facile way to achieve combined therapeutic functions for personalized nanomedicine.